2020
DOI: 10.23917/jep.v20i2.8517
|View full text |Cite
|
Sign up to set email alerts
|

Eradicating Income Inequality in Lower Middle-Income Countries

Abstract: Studying the distribution of income is an important issue to know what factors which affect to make income distribution more equitable, what factors can be the key to resolving the problem of income inequality, and shortening the distance between the poor and the rich. This paper studies the relationship between human capital, inflation rate, unemployment rate, physical capital, fiscal expenditure, gross domestic product growth, and urbanization on income inequality in 52 Lower Middle-Income Countries througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In fact, this phenomenon can damage productivity and innovation through a number of channels, such as unequal education, which can damage human capital accumulation process, and results in low productivity and decreased economic growth (Paus, 2017). Therefore, lack of education and health services combined with deficiency in redistributive policies, such as conditional cash transfer and tax reform have become major factors for increasing income inequality in emerging and low-middle income economies (Brueckner, Dabla-Norris, and Gradstein, 2014;Dabla-Norris, Kochhar, Suphaphiphat, Ricka, Tsounta, 2015;Fournier and Johansson, 2016;Pratysto and Panjaitan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this phenomenon can damage productivity and innovation through a number of channels, such as unequal education, which can damage human capital accumulation process, and results in low productivity and decreased economic growth (Paus, 2017). Therefore, lack of education and health services combined with deficiency in redistributive policies, such as conditional cash transfer and tax reform have become major factors for increasing income inequality in emerging and low-middle income economies (Brueckner, Dabla-Norris, and Gradstein, 2014;Dabla-Norris, Kochhar, Suphaphiphat, Ricka, Tsounta, 2015;Fournier and Johansson, 2016;Pratysto and Panjaitan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The higher the level of education, the higher the performance (Dhian et al, 2013). A study in middle-income countries revealed that the disparity of human capital contributed to income inequality (Pratysto and Panjaitan, 2019). Experience also influences worker earnings (Ratna and Fauziah, 2018).…”
Section: Jurnal Ekonomi Pembangunan Issn 1411-6081 E-issn 2460-9331 222mentioning
confidence: 99%
“…Differences in the endowment of natural resources and the demographic circumstances observed in each place can be the first causes of inequality [1]. Given that the allocation of economic resources will have a significant impact on income disparity, it is crucial to address this issue, particularly in emerging nations [2]. More focus is needed on why the government hasn't been able to considerably reduce poverty and income inequality, and in particular, what could be causing the poor economic growth that has an effect on poverty levels and income inequality [3].…”
Section: Introductionmentioning
confidence: 99%